Program Latihan Pengembangan Aparatur di Indonesia: Faktor Determinan Pergeseran dari Mengajari ke Fasilitasi - Nurmillah; Rifdan; Darman Manda (JSSHA ADPERTISI JOURNAL, 2021)
The Implementation of the Apparatus Development Competency Training Program in 2019 is a recommendation from the results of the evaluation of the same Program as stated in the Regulation of the Head of LAN RI Number 2 of 2019 concerning ASN Competency Development Training. An indication of the new pattern in the 2019 program concept was found in the methods adopted and technically practiced by Widyaiswara who acted as the facilitator who no longer played a role in instructing and dictating certain knowledge material but rather facilitating, not teaching. On the part of the participants, the classroom learning mechanism is accompanied by field activities in their respective institutions related to the tasks carried out